Respuesta :

Answer:

Option D: [tex]$ \frac{log \hspace{1mm} 3mn}{p} $[/tex]

Step-by-step explanation:

We have the following rules:

[tex]$ log \hspace{1mm} a + log \hspace{1mm} b = log \hspace{1mm}(a + b) $[/tex]

[tex]$ log \hspace{1mm} a - log \hspace{1mm} b = log\hspace{1mm} \bigg( \frac{a}{b} \bigg ) $[/tex]

Here, we have: [tex]$ log \hspace{1mm} 3 + log \hspace{1mm} m + log \hspace{1mm} n - log \hspace{1mm} p $[/tex]

[tex]$ = \bigg ( log \hspace{1mm} 3 + log \hspace{1mm} m + log \hspace{1mm} n \bigg ) - log \hspace{1mm} p $[/tex]

[tex]$ = log \hspace{1mm} 3mn - log \hspace{1mm} p $[/tex]

[tex]$ = log \bigg( \frac{3mn}{p} \bigg ) $[/tex]

Hence, the answer.